Readiness Among TESL Pre-Service Teachers in ESL Online Teaching - Mohd Fauzi, Nur Alya Diyana; Taharn @ Taha, Nur Asilah; Mohamad, Ayu Rita (Selangor Humaniora Review, 2022)
The COVID-19 pandemic has put a halt to the traditional face-to-face class engagement for educational institutions throughout the country. This situation has also severely affected educational faculties that require students to carry out their practicum service, TESL pre-service teachers are one of the many that are struggling to cope with this crisis as what they have been training for has not prepared them for teaching online classes. This study aims to investigate TESL pre-service teachers’ readiness to conduct ESL online classes and further find out what challenges they face in teaching online. In order to gather the data for this study, a triangulated mixed method research approach has been used that includes an online close-ended questionnaire that consists of 20 questions on TESL pre-service teachers’ readiness to conduct ESL online classes and interview sessions with 12 TESL pre-service teachers regarding the challenges of teaching ESL online classes. The quantitative data has been analysed by using the Statistical Package for the Social Sciences for Windows (SPSS) software while the qualitative data has been analysed by implementing the thematic analysis approach. The findings revealed that a significant number of the TESL pre-service teachers are not ready to teach students through online approaches and methods and agreed that they have not been exposed to the techniques to teach ESL online classes and require training on it. Thus, this study recommends that the university and faculty introduce a new subject for TESL pre-service teachers on the pedagogical methods and approaches to teach ESL online classes. Thus, this study is significant for the university and faculty to identify the readiness of TESL pre-service teachers in teaching online classes.